Emergence of multinational firms from middle income countries: the case of Poland. - Klimek, Artur (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
The paper analyses factors contributing to foreign activities of Polish enterprises. Most of the previous studies focused on the flows of outward foreign direct investment (OFDI) from advanced economies. Therefore, it was essential to investigate the role of firms from emerging Europe in this process. The research is conducted at the early stage of development of OFDI from Poland as a significant increase in foreign production has been recorded for a few years. The issue is investigated using firm-level data. The results confirm that firms investing abroad are significantly more productive compared to counterparts operating only in the home country
Argumenta Oeconomica, 2011, Nr 1 (26), s. 91-110
Keywords: foreign direct investment; heterogeneous firms; emerging countries; inwestycje bezpośrednie; inwestycje zagraniczne; kraje rozwijające się; przedsiębiorstwo międzynarodowe